Use of chloride ingress model for condition assessment in bridge management - Zambon, Ivan (2019)
Although there is a large number of established Bridge Management Systems worldwide, there seems to be a lack of those that utilise the knowledge on material properties and environmental loading. Hence, as a supplement to current practice, the paper examines the use of the chloride ingress model, supported by the International Federation for Structural Concrete, for preliminary assessment in bridge management. The focus is set on analysing application of the model in realistic situations on existing concrete bridges for which the information on material and environmental properties is lacking.